Effects of nonlinear frequency compression on Mandarin speech and sound-quality perception in hearing-aid users. (2nd July 2020) - Chen, Xueqing; You, Yanyan; Yang, Jing; Qian, Jinyu; Lu, Qian; Kuehnel, Volker; Rehmann, Julia; Liu, Bo; Xu, Li
Abstract: Objective: The purpose of the present study was to examine the effects of NLFC fitting in hearing aids and auditory acclimatisation on speech perception and sound-quality rating in hearing-impaired, native Mandarin-speaking adult listeners. Design: Mandarin consonant, vowel and tone recognition were tested in quiet and sentence recognition in noise (speech-shaped noise at a +5 dB signal-to-noise ratio) with NLFC-on and NLFC-off. Sound-quality ratings were collected on a 0–10 scale at each test session. A generalised linear model and correlational analyses were performed. Study sample: Thirty native Mandarin-speaking adults with moderate-to-severe sensorineural hearing loss were recruited. Results: The hearing-impaired listeners showed significantly higher accuracy with NLFC-on than with NLFC-off for consonant and sentence recognition and the recognition performance improved with both NLFC-on and off as a function of increased length of use. The satisfaction score of sound-quality ratings for different types of sounds significantly increased with NLFC-on than with NLFC-off. The speech recognition results showed moderate to strong correlation with the unaided hearing thresholds. Conclusion: For native Mandarin-speaking listeners with hearing loss, the NLFC technology provided modest but significant improvement in Mandarin fricative and sentence recognition. Subjectively, the naturalness and overall preference of sound-quality satisfaction judgement also improved with NLFC.